Catholic theatre and drama: critical essays - Wetmore, Kevin J. Jr. (McFarland & Co., 2010)
"This collection seeks to demystify the ties--both practical and ideological--that have long bound Catholicism to theatrical production, offering insights into medieval theatre, Jesuit drama, ballet and opera, modern stagings of medieval liturgical drama, Italian Catholic women's drama, Catholic playwrighting and acting, and the unique challenges of teaching theatre in Catholic universities" --Provided by publisher